Management of Traumatic Undiagnosed Condyle Fracture in Children - Rizal, Syamsul; Kreshanti, Prasetyanugraheni; Handayani, Siti; Bangun, Kristaninta (Lingkar Studi Bedah Plastik Foundation, 2012)
Background: Condyle trauma is considered to be the major cause of TMJ ankylosis but it is also the most neglected and under-managed problem in children. ?TMJ ankylosis leads to be malocclusion and facial disfigurement. The aim of early treatment is to restore the mandibular mobility and to enhance further growth in order to reduce the possibility of future facial asymmetry. Patients and Methods: We report two patients with inability to open mouth few months following injury. They most probably suffered missed diagnosis condyle fracture by the previous physician. The latest physical examination and radiological finding shows the mandible was micrognathic and unilateral TMJ ankylosis was confirmed. A sequential protocol of TMJ ankylosis management based on aggressive resection of ankylotic mass was performed and followed withphysiotherapy.Result: In 2 month-follow up, both patients showed significant improvement in mouth opening and the mastication function was restored, accompanied with physical therapy to gain maximum mouth opening for at least a year.Summary: A detail history, clinical and functional examination, radiographic examination facilitating correct diagnosis followed by immediate surgical intervention, and physiotherapy can help us to restore physical, psychological, and emotional health of the child patient.